Numerical Simulation of Gas Atomization and Powder Flowability for Metallic Additive Manufacturing - Yonglong Du; Xin Liu; Songzhe Xu; Enxiang Fan; Lixiao Zhao; Chaoyue Chen; Zhongming Ren (Metals)
The quality of metal powder is essential in additive manufacturing (AM). The defects and mechanical properties of alloy parts manufactured through AM are significantly influenced by the particle size, sphericity, and flowability of the metal powder. Gas atomization (GA) technology is a widely used method for producing metal powders due to its high efficiency and cost-effectiveness. In this work, a multi-phase numerical model is developed to compute the alloy liquid breaking in the GA process by capturing the gas–liquid interface using the Coupled Level Set and Volume-of-Fluid (CLSVOF) method and the realizable k-ε turbulence model. A GA experiment is carried out, and a statistical comparison between the particle-size distributions obtained from the simulation and GA experiment shows that the relative errors of the cumulative frequency for the particle sizes sampled in two regions of the GA chamber are 5.28% and 5.39%, respectively. The mechanism of powder formation is discussed based on the numerical results. In addition, a discrete element model (DEM) is developed to compute the powder flowability by simulating a Hall flow experiment using the particle-size distribution obtained from the GA experiment. The relative error of the time that finishes the Hall flow in the simulation and experiment is obtained to be 1.9%.